ADVANTAGES OF IMPLEMENTING TRAINING TECHNOLOGIES IN THE MILITARY EDUCATION SYSTEM - Okhramovych, M.; Sokolina, O. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2019)
Opportunities and perspectives of the use of distance learning technologies (DLT) in the process of professional training of military experts are considered in the paper. DLT allows to carry out educational process at a distance without losing its quality. DLT even improves quality due to individualization, active teaching methods, bilateral interaction between teacher and student (cadet). The distance learning form will be considered as an additional system that is used to supplement the academic disciplines taught by the Secondary Schools for applicants’ education in full-time education. The main aim of the using distance learning technologies at the Secondary School is providing students with access to electronic educational resources through the using modern information technologies and telecommunication networks. The educational process in distance learning for a cadet have to include all the main forms of the traditional organization at the educational process: lectures, seminars and practical classes, laboratory workshops, control system, research and independent work. All these forms of organization of the educational process will allow to implement a flexible combination of independent cognitive activity of students (cadets) in with different sources of information, operational and systematic interaction with the course teacher and group work of students (cadets). The advantages of using distance learning technologies in the training of military specialists are various, namely: flexibility, modularity, technological approach, increase motivation and self-motivation of students, new role of the teacher. The process of using remote technology is considered as an integral part of the assessment of the quality education and information during the educational process. The new possibilities of practical application of remote technologies in the organization educational process in the Secondary School are formulated in this paper.